PROBLEM SITUATIONS: SIGNIFICANT POSSIBILITIES TO THE TEACHING/LEARNING IN SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
This study had as its aim to search pedagogical approaches with significant contributions to the School Physical Education. The presented proposals were suited in the autonomy principles and diversity respect. In this perspective, the teaching through problem-situations was characterized as profitable to attend the presuppositions. Through a field research, with a qualitative approach, it was made an analysis, inside the public schools, to verify whether the pedagogical practices developed propitiated problem-situations in the Physical Education classes. It was reached a conclusion that, although the performed activities had benefited the problem-situations presence, the teachers' intervention was not totally appropriated to reach the objectives.
Keywords: School Physical Education; Pedagogical Practices; problem-situations